Legal Analysis of the Authority of Military Judges in the Procedural Law of Examination of Connectivity in Corruption Cases - Fikri, Humaidi; Sagala, Parluhutan; Suswantoro, Tri Agus (CV. Rayyan Dwi Bharata, 2025)
In order to uphold law enforcement, especially in the field of criminal law, the law distinguishes between civilians and the military. The problem that arises now is what if a criminal act is committed by the military together with civilians, which in its development is called a connectivity case. The corruption case that occurred in Indonesia involving the military and civilians that has been decided by the Connectivity Court is the Corruption Case of the Indonesian Army Compulsory Savings from 2013 to 2020 with the Defendant from the Military, namely Brigadier General TNI (Ret.) Yus Adi Kamrullah, S.E., M.Sc., and from the civilian party Ni Putu Purnamasari which caused the state a loss of Rp. 127,000,000,000,- (one hundred and twenty seven billion rupiah), and the corruption case of the 123 East Longitude Orbit Slot Satellite Procurement Project/Floater Satellite Procurement between the Indonesian Ministry of Defense in 2012 to 2021 involving the military and civilians with the Defendant Rear Admiral (Ret.) Agus Purwoto, and from the civilian side the Defendants Arifin Wiguna and Surya Cipta Witoelar which caused the state a loss of Rp.453,094,059,540.68 (four hundred fifty three billion ninety four million fifty nine thousand five hundred forty point sixty eight cents). The purpose of this study is to determine the implementation of handling corruption criminal cases through connectivity courts in Indonesia and the authority of military judges in connectivity courts and to determine the resolution of connectivity criminal cases in corruption crimes committed by civilians and military personnel in both cases in the Connection Court. The study uses a normative legal research method. The data used are secondary and primary data, then the data is processed and presented in the form of a literature study. The analysis used is deskriftif juridis and fersfektif analysis. The results of the study indicate that the process of handling connectivity cases in corruption cases of connectivity has been partially carried out in accordance with the applicable criminal procedure law (KUHAP) and the defendants are legally and convincingly guilty of committing corruption together in accordance with Article 2 Paragraph (1) in conjunction with Article 18 of Law Number 31 of 1999 as amended by Law Number 20 of 2001 in conjunction with Article 55 Paragraph (1) ke-1 of the Criminal Code.